Electronic Government c - Janssen, Marijn; Scholl, Hans J.; Wimmer, Maria A.; Tan, Yao-hua.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 10th International Conference, EGOV 2011, held in Delft, The Netherlands, in August/September 2011. The 38 revised full papers presented were carefully reviewed and selected from 84 submissions. The papers are organized in topical sections on foundations, acceptance and diffusion, governance, openess and institutions, architecture, security and interoperability, transformation, values and change.
Keywords: Computer science; Computer Communication Networks; Information systems; Computers -- Law and legislation; Information Systems; Computer Science; Computers and Society; Management of Computing and Information Systems; Legal Aspects of Computing; Computer Communication Networks; User Interfaces and Human Computer Interaction; Computer Appl. in Administrative Data Processing